CORRELATION BETWEEN VITAMIN D DEFICIENCY AND TYPE 1 DIABETES IN CHILDREN - Tatiana Chisnoiu; Cristina Maria Mihai; Adriana Luminita Bălașa; Alexandru Cosmin Pantazi; Antonio Andrusca; Bianca Maria Constantin; Andreea Dalila Nedelcu; Simona Claudia Cambrea (Romanian Society of Oral Rehabilitation, 2023)
Background: Vitamin D is an organic compound with an important role in bone metabolism and ability to modulate the immune function. Epidemiology research have recently suggested vitamin D's role in the etiology of type 1 and type 2 diabetes in children. Vitamin D controls insulin secretion in pancreatic islets and insulin sensitivity in several peripheral metabolic organs by acting through the vitamin D receptor (VDR). Recent studies have reported an increased prevalence of vitamin D deficiency among patients diagnosed with type 1 diabetes. The aim of the study is to identify the correlation between vitamin D deficiency and the frequency, severity, and control of type 1 diabetes in children. Material and Methods: The retrospective study was performed on 40 subjects with type 1 diabetes, which associated vitamin D deficiency at the onset of the disease or during the investigation period, at Pediatric Clinic of Constanta County Clinical Emergency Hospital. The strategy used involved the collection of certain parameters from the observation sheets, in order to evaluate, compare and illustrate the correlation between vitamin D deficiency and type 1 diabetes. Results: Male subjects represented the majority of cases (55%). The seasonal incidence may be explained by exposure to a reduced amount of ultraviolet radiation in the cold season, which contributes to the decrease in the level of 25-hydroxyvitamin D. Viral infections had an increased incidence in the winter, which may contribute to the onset of type 1 diabetes. An optimal level of serum 25-hydroxyvitamin D was found in 17% cases, insufficient level in 63% cases and deficiency in 20% cases. In evolution, 24 cases had poor glycemic control, registering values higher than 7% of glycosylated hemoglobin. The dosage of 25 hydroxyvitamin D in these subjects indicated vitamin D deficiency in 7 cases and insufficiency in 17 cases. None of the patients with a glycosylated hemoglobin value >7 had an optimal 25-hydroxyvitamin D level. Out of 16 patients with optimal glycosylated hemoglobin values (<7%), 2 cases presented vitamin D deficiency, 6 cases insufficient level, and 8 cases had an optimal value of 25-hydroxyvitamin D. Conclusions: Vitamin D deficiency is associated with the evolution of type 1 diabetes in children. The evaluation of vitamin D levels is a potential disease-modifying factor in type I diabetes therapeutic management.